Integrated protection of winter wheat from weeds - I. V. Fetyukhin; A. A. Baranov (Зерновое хозяйство России)
The low resistance of plants to weeds and the high potential contamination of the soil by the most harmful weeds is the most important reason for the shortage of the crop yield. The subject of research was the development of integrated weed control measures based on the analysis of the structure of the weed component in winter wheat. The study has shown that infestation with juvenile and offset weeds of is predominant in the studied area. Due to the occurrence of weeds, it was found that the largest proportion of juvenile weeds in winter wheat sowings is represented by penny cress (Thlaspi), and the perennial weeds are represented by Canadian thistle (Cirsium arvense). According to the study results of the agrophytocenosis, such weeds as Canadian thistle (Cirsium arvense) and goosefoot (frost blite) are the most harmful in the upper layer during winter wheat earing period. During this period in the middle and lower layers there were such weeds specific for winter as penny cress (Thlaspi), flixweed (herb-Sophia) and henbit dead-nettle (common henbit). There has been proposed a combination of preventive, phytocenotic, mechanical and chemical measures for weed control to protect winter wheat crops against weeds of various biological groups, including those specialized for the very crops. It has been established that with a mixed type of weed infestation and 32.2 pcs/m2 of weeds in winter wheat crops, there is an economic threshold of harmfulness, which determines the necessity to apply integrated weed control measures. The introduction of the developed measures to control weeds provides an increase in profitability level of winter wheat cultivation on 15...20%.